2004
DOI: 10.1002/ppul.10424
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary function in bronchopulmonary dysplasia

Abstract: The purpose of this study was to examine lung function and bronchodilator responsiveness in infants with a history of prematurity and bronchopulmonary dysplasia (BPD), using the raised volume rapid thoracoabdominal compression technique as well as with whole-body plethysmography. Spirometric measurements were obtained in 28 infants with a history of BPD, defined as preterm birth with O2 requirement at 36 weeks postmenstrual age (gestational age at birth, 26.4 +/- 2.1 weeks, mean +/- SD; birthweight, 898 +/- 35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
121
2
9

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(139 citation statements)
references
References 23 publications
7
121
2
9
Order By: Relevance
“…20,21 Abnormalities in airflow obstruction and air trapping persist into adolescence. [22][23][24][25][26] Similarly, newborn animals exposed to Ն65% oxygen and recovered in room air develop long-term changes in airway responsiveness and increased lung volumes. [27][28][29][30][31] We previously reported that 8-week-old adult mice exposed to Ն60% oxygen for the first 4 days of life have simplified alveoli attributed to changes in elastin expression and an imbalance in alveolar epithelial type I and II cells.…”
mentioning
confidence: 99%
“…20,21 Abnormalities in airflow obstruction and air trapping persist into adolescence. [22][23][24][25][26] Similarly, newborn animals exposed to Ն65% oxygen and recovered in room air develop long-term changes in airway responsiveness and increased lung volumes. [27][28][29][30][31] We previously reported that 8-week-old adult mice exposed to Ն60% oxygen for the first 4 days of life have simplified alveoli attributed to changes in elastin expression and an imbalance in alveolar epithelial type I and II cells.…”
mentioning
confidence: 99%
“…Although advances in the care of neonates have markedly reduced infant mortality, survivors often exhibit nonatopic airway wheezing (9,10), and many are rehospitalized when infected with respiratory syncytial virus (11,12). High blood pressure has also been observed in young adolescents who were born preterm (13).…”
mentioning
confidence: 99%
“…Fortunately, antenatal steroid administrations to mothers in preterm labor, and the application of exogenous surfactant and mild ventilation strategies to premature babies, have markedly reduced their mortality. Unfortunately, survivors continue to show decreased lung capacity at 5-10 years of age and even as young adolescents (2)(3)(4). Moreover, these children are at increased risk for asthma, infection, and other respiratory diseases, and are often rehospitalized after respiratory infection (5,6).…”
mentioning
confidence: 99%